Respon Bioinvogurasi Benih dengan Plant Growth Promoting Rhizobacteria (PGPR) terhadap Pertumbuhan dan Produktivitas Padi Gogo - Fitriani Fitriani; Yulida Amri; Syamsul Bahri; Fara Nadilla (BIOEDUSCIENCE, 2021)
Background: Gogo rice is a type of rice that can be cultivated on dry land with a yield productivity level of 2.57 tons / Ha. So it is necessary to make efforts to increase the growth and productivity of gogo rice through seed bio-inviguration using PGPR. The purpose of this study was to determine the effect of beni bioinviguration techniques using PGPR on the growth and productivity of gogo rice. Method: This study used a RAK consisting of 7 treatments and 5 replications. Data analysis used ANOVA at the 5% confidence level and continued with the BNT test. Result: The results showed that the use of biomatriconditioning medium integrated with PGPR could increase the stem height of upland rice by 104.2 cm, 117 cm, and 133.3, the number of tillers were 7, 13 and 15 at the age of 8, 10, and 12 MST. In addition, it can also increase the number of panicles, the length and weight of 100 grains of 14, 22.6 cm and 2.1 grams. Conclusion: the use of biomatriconditioning medium integrated with PGPR can increase the growth and productivity of gogo rice.